A lifestyle intervention for primary care patients with depression and anxiety: A randomised controlled trial. Issue 2 (15th December 2015) - Forsyth, Adrienne; Deane, Frank P; Williams, Peter
Abstract: This study aimed to evaluate the efficacy of a diet and exercise lifestyle intervention on mental health outcomes for patients currently being treated for depression and/or anxiety in primary care. Patients ( n =119) referred by general practitioners to the 12-week randomised controlled trial were assigned to either an intervention of six visits to a dual qualified dietitian/exercise physiologist (DEP) where motivational interviewing and activity scheduling were used to engage patients in individually-tailored lifestyle change (focussed on diet and physical activity), or an attention control with scheduled telephone contact. Assessments conducted at baseline ( n =94) and 12 weeks ( n =60) were analysed with an intent-to-treat approach using linear mixed modelling. Significant improvement was found for both groups on Depression, Anxiety and Stress Scale (DASS) scores, measures of nutrient intake and total Australian modified Healthy Eating Index (Aust-HEI) scores. Significant differences between groups over time were found only for iron intake and body mass index. Patients participating in individual consultations with a dietitian were more likely to maintain or improve diet quality than those participating in an attention control. This study provides initial evidence to support the role of dietitians in the management of patients with depression and/or anxiety. Highlights: Patients with depression and anxiety participated in a 12-week RCT.Patients attended six individual consultations with dietitian/exercise physiologists. Sessions incorporated motivational interviewing and activity scheduling. Depression and anxiety symptoms and dietary intake were measured. Scores improved for patients in both the intervention and attention control groups.